2002
DOI: 10.1039/b203700a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and chemical characterization of active and inactive Cu species in NO decomposition catalysts based on Cu-ZSM5

Abstract: The number and type of Cu 2+ species present on O 2 -treated Cu-ZSM5 catalysts (Si/Al ¼ 13.1-14.6) with varying Cu/Al ratios (0.12-0.60) were measured using temperature-programmed reduction in H 2 or CO and desorption of O 2 with He as the carrier. The effluent stream was monitored using mass spectrometry and the structure and oxidation state was determined in parallel by X-ray absorption spectroscopy. Isolated Cu 2+ monomers and oxygen-bridged Cu 2+ dimers interacting with Al-Al next nearest neighbor pairs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
147
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(159 citation statements)
references
References 45 publications
10
147
2
Order By: Relevance
“…The cyclohexyl hydroperoxide response was calibrated using parallel iodometric titrations of liquid samples extracted from the reactor. 9 Typical H 2 -TPR kinetic data are shown in Figure 1. On MnAPO samples, a H 2 consumption peak appeared at ∼580-600 K; Co cations reduced at higher temperatures (∼750 K).…”
Section: Synthesis and Characterization Of Meapo Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclohexyl hydroperoxide response was calibrated using parallel iodometric titrations of liquid samples extracted from the reactor. 9 Typical H 2 -TPR kinetic data are shown in Figure 1. On MnAPO samples, a H 2 consumption peak appeared at ∼580-600 K; Co cations reduced at higher temperatures (∼750 K).…”
Section: Synthesis and Characterization Of Meapo Samplesmentioning
confidence: 99%
“…To some extent, the structural complexity arising from multiple cation types and from ubiquitous changes in cation valency during treatment and catalytic turnovers prevent any one spectroscopic method from providing a rigorous assessment of cation speciation and catalytic relevance. Quantitative chemical methods have proven essential to provide such information for cation-modified aluminosilicates, 9 but they have not been rigorously used for cation-modified aluminophosphate materials.…”
Section: Introductionmentioning
confidence: 99%
“…NO The reducibility of the Cu in ZSM-5 and IM-5 has been studied with H 2 -TPR using 1 % H 2 , which 558 is shown in Figure 10. In the fresh Cu-ZSM-5 and Cu-IM-5, the Cu is reduced in two stages giving The reason why the first reduction is seen as only one peak and not as two, as would be expected 570 when Cu-dimers are present, is because the limiting step is the dissociation of H 2 and not the 571 reduction itself in the first step [55]. show reduction in this temperature range [56,57].…”
mentioning
confidence: 99%
“…Cu-ZSM-5 and especially on the identity and possibility of dimer formation, which has been and is 644 still being discussed extensively [30,17,55,60,61,62]. For this reason the first paragraph will be 645 devoted to the subject of speciation followed by discussion of the deactivation mechanism wherein 646 an attempt to disentangle the contributions from dealumination and copper migration will be made.…”
mentioning
confidence: 99%
“…Some studies [27][28][29][30] have suggested that the ELO is associated with mononuclear copper and is of the structure Cu 2+ -O − or Cu 2+ -O 2− . Alternatively, others [21,22,33,[39][40][41] proposed that a single-O-bridged copper pair, i.e., [CuOCu] 2+ , is essential in the NO decomposition cycle. Recent computational contributions of Goodman et al [38,42] stressed the eventual role of double-O-bridged copper pairs, i.e., [CuO 2 Cu] 2+ .…”
Section: Introductionmentioning
confidence: 99%